PENGARUH PERSEPSI DUKUNGAN ORGANISASIONAL TERHADAP KOMITMEN AFEKTIF DENGAN KEPUASAN KERJA SEBAGAI PEMEDIASI PADA PT. TELKOM INDONESIA TBK PUSAT TERNATE - Sunarti Salim; Rahmat Sabuhari (Jurnal Manajemen Sinergi, 2022)
The purpose of this study was to determine and analyze:(1) the positive and significant effect of perceived organizational supporton affective commitment; (2) the effect of perceived organizationalsupport positively and significantly on job satisfaction; (3) The effect ofjob satisfaction positively and significantly on Affective Commitment;and (4) Perception of Organizational Support positively and significantlytowards Affective Commitment through job satisfaction at PT TelkomIndonesia, Ternate City.The data analysis technique used in this studyis SEM analysis using Smart Partial Least Square (PLS) version 3 as astatistical test tool.Methodology: The analytical model used are Structural EquationModeling with SMART PLS as tools for the statistical test. Datacollection tools used are questionnaires and interviews, and the numberof respondents was 151 employee.Finding: The results of the SEM-SMART-PLS calculation show that thet-statistic value of 5.854 is greater than the t-table of 1.96 and the valueof = 5% is smaller than the p-value of 0.000. This means that hypothesis1 is accepted.Furthermore, the second hypothesis testing shows the tstatisticvalue of 8,047 which is greater than the t table value of = 5%,which is smaller than the p-value of 0.000. Testing the third (H3)hypothesis shows that the t-statistic value of 6.708 is also greater thanthe t-table value of = 5% smaller than the p-value of 0.000. This meansthat hypothesis 3 is accepted. Testing the fourth hypothesis (H4),namely the t-statistic value of 4,870, the value of = 5%, which is smallerthan the p-value of 0.000. This means that hypothesis 4 is accepted.Conclusion: The conclusions in this study are: (1) Perception oforganizational support has a significant positive effect on affectivecommitment; (2) Perception of organizational support has a significantpositive effect on job satisfaction; (3) Job satisfaction has a significantand positive effect on affective commitment; and (4) job satisfaction isa variable mediating the effect of perceived organizational support onaffective commitment.